Traditions and Taboos of the Mah Meri Tribe of Tanjung Sepat, Banting, Selangor: (Amalan Tabu Suku Mah Meri Tanjung Sepat, Banting Selangor) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
This study aims to describe some aspects of the traditions and taboos concerning marriage, funerals, births and work among the Mah Meri community of Tanjung Sepat. Utilizing a qualitative approach, data was collected through the in-depth interview method. For supporting purposes, data obtained through content analysis also used in the study. The results of the study indicate that traditions and taboos are still of the utmost importance in the Mah Meri community. This correlates with the belief system passed down from one generation to another which ensures the continuity of those practices in the community. Since the Mah Meri community is well-known for their pride in their own identity, the continuity of such practices in the community can be seen as a defence mechanism to sustain their indigenous knowledge and traditions. These findings not only englighten about the customs and traditions of the Mah Meri community, but also contribute greatly to the store of knowledge concerning the sociology of the Malay world.Keywords: taboos, traditions, customs, Mah Meri, marriage, birth, death, work